1992
DOI: 10.1103/physrevb.45.507
|View full text |Cite
|
Sign up to set email alerts
|

Critical exponents inCd1xMn

Abstract: We argue that the conventional dynamic scaling expressions in spin glasses are relevant only above the temperature at which a maximum of the imaginary part of the ac magnetic susceptibility is observed. Then different methods to derive the critical exponent zv in Cd06Mn0. 4Te independently from the spin-glass temperature give the same result zv=10. We also discuss the values of the critical scaling exponents P and y.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Restricting the scaling analysis to x"(T) data corresponding to temperatures above the maxima in these curves results in zv -10. 24 Another reason for not including x"(T) data corresponding to temperatures close to and below T g , is the influence of ageing resulting in xi u ) being time dependent. 25 Using such data in the scaling analysis will inevitably yield departures from scaling.…”
Section: Resultsmentioning
confidence: 99%
“…Restricting the scaling analysis to x"(T) data corresponding to temperatures above the maxima in these curves results in zv -10. 24 Another reason for not including x"(T) data corresponding to temperatures close to and below T g , is the influence of ageing resulting in xi u ) being time dependent. 25 Using such data in the scaling analysis will inevitably yield departures from scaling.…”
Section: Resultsmentioning
confidence: 99%
“…We comment that Geschwind and co-workers, 28 using linear scaling plots, found ␥ϭ4.4 in Cd 1Ϫx Mn x Te. This higher value of ␥ was debated by Bertrand et al, 10 who suggested that the larger value of ␥ obtained by Geschwind et al was due to the use of an incorrect value for T c in the scaling plot. This debate notwithstanding, we conclude that within our experimental error, there is fair agreement between values for the critical exponent ␥ obtained in Zn 1Ϫx Mn x Te and Cd 1Ϫx Mn x Te.…”
Section: B Magnetization Measurementsmentioning
confidence: 95%
“…However, as the critical point is approached, different model-dependent scaling functions should approach constant values. In addition, on the basis of an analysis of the spin autocorrelation function, Bertrand et al 10 have argued that Eq. ͑3͒ is only valid for temperatures TϾT p , where T p is the temperature at which the peak in Љ(,T) occurs.…”
Section: A Ac Susceptibility Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only data at temperatures above that of the peak in ′′ χ ( f , T ) were included in the scaling plot. 33 . The best scaling was obtained for the following values: 19 which is likely an indication of deep underlying similarities in the nature of the interactions and the interacting entities in both systems.…”
mentioning
confidence: 99%